Węzłowe problemy funkcjonowania gospodarki terenowej - Wierzbicki, Janusz (Wydział Prawa i Administracji UAM, 1981)
The author explains mechanism of local economy functioning and distinguishes three sets in this mechanism: decentralized, centralized and mixed sets. Taking into account conditions of local economy functioning, in which local authorities are decisive subjects (local administration and people's councils) the author formulates an opinion that postulates on decentralization, which are stated in discussions, practically refer to substitution of centralized set with mixed set — and not decentralized one — of local economy. Centralized set can not be fully abolished even when mixed set is a predominating set of local economy functioning. Anyway it does not eliminate the possibility of competence expansion of leading local authorities. In such situation decentralized set of local economy functioning, in strict meaning of the word, can play a marginal role only. The author considers in a broad way the role played by financial factor in local economy functioning. A special attention is paid to dissimilarity of financing principles in particular sets of this economy, because efficiency of the reform considerably depends on proper knowledge about these principles.
Crucial Problems of the Local Economy Functioning